2009
DOI: 10.1109/tcad.2009.2013540
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Multiple-Voltage Design With Bridge Defect

Abstract: Abstract-Multiple-voltage is an effective dynamic power reduction design technique, commonly used in low power ICs. To the best of our knowledge there is no reported work for diagnosing multiple-voltage enabled ICs and the aim of this paper is to propose a method for diagnosing bridge defects in such ICs. Using synthesized ISCAS benchmarks, with realistic extracted bridges and a parametric fault model, the paper investigates the impact of varying supply voltage on the accuracy of diagnosis and demonstrates how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…It is critical to silicon debugging, yield analysis and for improving subsequent manufacturing cycle [6]- [8]. Recent research has reported a number of DFT solutions to test power-switches when considering the two possible type of faults: stuck-open and stuck-short [5], [9]- [11].…”
mentioning
confidence: 99%
“…It is critical to silicon debugging, yield analysis and for improving subsequent manufacturing cycle [6]- [8]. Recent research has reported a number of DFT solutions to test power-switches when considering the two possible type of faults: stuck-open and stuck-short [5], [9]- [11].…”
mentioning
confidence: 99%
“…After generating the discrete open resistance set (line 1), the procedure starts in the first part by fault simulating all fault locations (ROF s), test patterns (T P s) using V DD settings (V DDs) and open resistance values (ROs) to obtain the path delay information (P D) as shown in lines (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Once the delay values (P D) for fault free paths (∀RO = 0) and faulty paths (∀RO ∈ ROs) are obtained, the longest path delays at each V DD of long paths (LP D G (V DD)) considering (T P ∈ T P s G ) and of short paths (LP D S (V DD)) considering (T P ∈ T P s S ) are identified using the fault free path delay data P D (∀RO = 0) as shown in line [19][20][21][22].…”
Section: Fig 7 Prior Spectre Simulationmentioning
confidence: 99%
“…To optimize the screening and detection of resistive open faults (ROFs), testing methods employing multiple supply voltages have been investigated and proved to give good results [5], [6], [7], [8]. With the emergence of low power designs which utilize multiple supply voltage levels [9], multi-V DD -based methods are ow of critical concern for effective testing and diagnosis [10], [11], [12], [13], [14].…”
mentioning
confidence: 99%
“…Some of the software tools developed during the course of this Ph.D. project have already been used in studies that were not conducted by the author of this thesis. Such studies include research on diagnosis for resistive bridges and methods to reduce the number of supply voltage settings used while testing [92,93,94,95].…”
Section: Contributions In This Thesismentioning
confidence: 99%